Gendered Public Support for Criminalizing "Revenge Porn". (December 2019) - Lageson, Sarah Esther; McElrath, Suzy; Palmer, Krissinda Ellen
Many states have criminalized "revenge porn, " an increasingly common form of online sexual abuse. Yet, we know little regarding attitudes toward these laws. Through an original survey of nearly 500 U.S. residents, we find widespread public support for criminalization, but support varies by respondent's self-identified gender and revenge porn type. Women favor criminalization more than men, but support falls among women and men when the subject created the media, colloquially known as "selfies" or "noodz." Results suggest that women expressing their sexuality are deemed less deserving of protection, reinforcing feminist legal critiques of criminal law as insufficient to prevent sexual abuse.